Not All Responses to Breach are the Same: The Interconnection of Social Exchange and Psychological Contract Processes in Organizations - Dulac, Tanguy; Coyle-Shapiro, Jacqueline A-M.; Henderson, David J.; Wayne, Sandy J. (Academy of Management Journal, 2008)
We examined psychological contract breach and violation as they occur within social exchange relationships to account for employee outcomes. Results of a longitudinal study suggested that contract breach partially mediated the effects of perceived organizational support (POS) and leader-member exchange (LMX) (time 1 measures) on intentions to quit (time 2 measure). POS and LMX moderated the relationship between breach and violation (time 2 measure). Violation fully mediated the effects of breach on commitment and trust and partially mediated the effect of breach on turnover intentions. These findings highlight the interconnection of social exchange and psychological contract processes.